(untitled) (Journal of Oriental Studies, 2016)
В статье дается краткий обзор научных иссле- дований по мифологической прозе тюркских народов. Оценивая вклад ученых, которые в национальном ас- пекте изучали и изучают мифологическую прозу, автор статьи рассматривает их типологические разработки в этой области и сопоставляет терминологию мифологи- ческой прозы тюркоязычных народов. The article gives a brief overview of scientific researches on mythological prose of Turk people. Assessing the contribution of scientists who have studied in a national perspective and exploring the mythological prose, the author examines their typological development in this area and compares the terminology of the mythological prose Turkic peoples.